Pediatric Biliary Interventions in the Native Liver - Kang, Lisa H.; Brown, Colin N. (Seminars in Interventional Radiology, 2016)
Biliary disease in infants and children frequently presents diagnostic and therapeutic challenges. Pediatric interventional radiologists are often involved in the multidisciplinary teams who care for these patients. This article reviews several notable causes of biliary disease in children who have not undergone liver transplantation, describes the role of percutaneous interventional procedures in managing these conditions, and details applicable biliary interventional techniques.
Keywords: pediatric biliary interventions; bile ducts; interventional radiology; pediatric